Booster of Employee Loyalty: Application to Job Stress and Job Satisfaction of Bank Employees in East Java - , Nurdina; , Noerchoidah; Estiasih, Soffia Pudji; Soloty, Cindy Fransiskho; Arsy, Tegar Muhammad (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study explores the direct and indirect effects of job stress on employee loyalty with the mediation of job satisfaction of bank employees in East Java. Design/methodology/approach: This research is explanatory. The research was conducted on bank employees in East Java, the population. Data was collected through questionnaires and purposive sampling. The number of samples required was 160 respondents. SmartPLS software is used to analyze data and answer research hypotheses. Research Findings: The results provide empirical evidence that job stress has no significant effect on job satisfaction, job satisfaction significantly affects employee loyalty, and job satisfaction can mediate between job stress and job satisfaction. Theoretical Contribution/Originality: The practical implications can be used as a consideration for banking management in generating employee loyalty.